2013
DOI: 10.5858/arpa.2013-0093-cp
|View full text |Cite
|
Sign up to set email alerts
|

Validating Whole Slide Imaging for Diagnostic Purposes in Pathology: Guideline from the College of American Pathologists Pathology and Laboratory Quality Center

Abstract: Context.-There is increasing interest in using whole slide imaging (WSI) for diagnostic purposes (primary and/ or consultation). An important consideration is whether WSI can safely replace conventional light microscopy as the method by which pathologists review histologic sections, cytology slides, and/or hematology slides to render diagnoses. Validation of WSI is crucial to ensure that diagnostic performance based on digitized slides is at least equivalent to that of glass slides and light microscopy. Curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
495
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(521 citation statements)
references
References 52 publications
2
495
3
1
Order By: Relevance
“…The adjusted WSI major discrepancy rate in our study of 2.7% (2 of 74) by case is similar to the Bauer et al 8 results of 1.65% (5 of 303) and to the Campbell et al 13 results of 1.5% (3 of 212) for primary diagnosis. The results of these studies and ours are notably better than the average agreement rates found in the Pantanowitz et al 17 statistical meta-analysis of the publications to date, given in the College of American Pathologists guidelines for WSI validation, which showed WSI to be 3% (89% versus 92%) less accurate than GS examination, which is noteworthy because the clinical trial presented here was on intrinsically more difficult, consultation cases. There are a number of potential explanations for these differences.…”
Section: Commentcontrasting
confidence: 47%
“…The adjusted WSI major discrepancy rate in our study of 2.7% (2 of 74) by case is similar to the Bauer et al 8 results of 1.65% (5 of 303) and to the Campbell et al 13 results of 1.5% (3 of 212) for primary diagnosis. The results of these studies and ours are notably better than the average agreement rates found in the Pantanowitz et al 17 statistical meta-analysis of the publications to date, given in the College of American Pathologists guidelines for WSI validation, which showed WSI to be 3% (89% versus 92%) less accurate than GS examination, which is noteworthy because the clinical trial presented here was on intrinsically more difficult, consultation cases. There are a number of potential explanations for these differences.…”
Section: Commentcontrasting
confidence: 47%
“…4 Those guidelines suggested, among other things, that laboratories implementing WSI for diagnostic purposes should perform their own intraobserver variability (validation) studies, and that those studies should be appropriate for the intended clinical use of WSI in the laboratory. Validation studies should involve specimen preparations relevant to the intended use, and ''if a new intended use is contemplated, and this new use differs materially from the previously validated use, a separate validation for the new use should be performed.…”
mentioning
confidence: 99%
“…It should be noted that when making diagnoses by conventional microscopy, differences in the interpretation of individual cases can occur, which will increase to more problematic any specimen is found to be. Recommendations exist for using WSI systems in diagnostics including, amongst others, guidelines from the College of American Pathologists (CAP), the Digital Pathology Association and the Royal College of Pathologists [49]. According to CAP guidelines, internal quality control should be undertaken for any laboratory deciding to carry out digital diagnostics.…”
Section: Validationmentioning
confidence: 99%